O SER HUMANO COMO IMAGEM DE DEUS UMA ANÁLISE TEOLÓGICA DO DUALISMO ANTROPOLÓGICO NO DISCURSO RELIGIOSO DA COMUNIDADE CRISTÃ PAZ E VIDA - COELHO, ANDRÉ MAGALHÃES (2017)
This research proposes to investigate the theological anthropology of the Christian Community Peace and Life, evangelical group of neo-Pentecostal matrix. The theological emphasis on the unity of the human constitution, which biblical testimony indicates, contrasts with the historical experience of Christendom in which the body has always played a secondary role, a status that still remains in various religious groups, including current Brazilian Pentecostalism. In view of this reality, Pentecostalism establishes its foundations, faithful to its ecclesiastical context in the same Platonic tendency to value more what is usually called the "soul" and "spirit" than the body, despite the value of body healing, Corporeality in the liturgy and the logic of material prosperity also present in these religious experiences. In order to counter this view, the concept of integrated anthropology will be indicated, based on several authors, especially the theologian Alfonso Garcia Rubio. This concept is fundamentally characterized by the understanding that the human being is a unit. It is that concrete being that appears in all its corporeal dimensions, and the body must relate to the whole cosmos and other living beings making present in a world of relationships and not of exclusions and dichotomies. In this sense, we wonder to what extent the contribution of an integral theological anthropology can constitute a contribution to overcome the anthropological dualism in religious groups such as the Christian Community Peace and Life? The research indicates some theological paths of overcoming concepts of dualistic and reductionist nature of the human condition, in view of an integrated anthropology. As an overcoming of this dualism we suggest an incarnated spirituality where the body makes evident in all its relations and where the unitary experience of the human being as a concrete person. From the concept of Integrated Human, which seeks to overcome dualisms, it is hoped to offer the Christian Community Peace and Life, from its own experience, with all the ambiguities in it, a unitary perception of the human being.